Influence of tobacco chewing on oral health: A hospital-based cross-sectional study in Odisha - Shilpa Mahapatra; Preetha Elizabeth Chaly; Smruti Chandan Mohapatra; M Madhumitha (Wolters Kluwer Medknow Publications, 2018)
Background: Smokeless tobacco use in the Indian subcontinent is a part of many religious and cultural rituals and has gained a degree of social acceptance. The deleterious effects of smokeless tobacco are not as well-known as those produced by smoking. Objectives: The study was carried out to assess the influence of tobacco chewing on the oral health of adult patients attending the dental outpatients department of Khordha district headquarter, Odisha. Methods: A hospital-based cross-sectional study was conducted among 25-64-year-old patients attending the dental outpatient department of Gopabandhu Khordha district headquarter hospital. A total of 512 study participants, who were age and sex matched, were stratified into four age groups such as 25-34 years, 35-44 years, 45-54 years, and 55-64 years old. Oral health status of the participants was assessed using modified WHO Oral Health Assessment Form (2013). Pearson's Chi-square test, binary and multinomial logistic regression was performed to determine the relationship between oral health problems and tobacco chewing. Results: Among the tobacco chewers, 59.8% had gingival bleeding, 40.6% had periodontal pockets, 30.1% had loss of attachment, 48.4% had attrition, and 4.3% had potentially malignant disorders. Compared to the nonchewers, these oral problems were significantly higher among the chewers. Whereas dental caries experience was significantly lower among the chewers (40.6%) compared to the nonchewers (54.7%). Compared to the nonchewers, chewers had 1.71 times increased odds for gingival bleeding, 1.71 times increased odds for periodontal pockets, 2.39 times increased odds for loss of attachment, and 2.49 times increased odds for attrition, which were statistically significant. Conclusion: Hence, the study revealed that tobacco chewing definitely had an influence on oral health, with statistically significant increase in oral health problems in chewers compared to nonchewers. Moreover, loss of attachment and potentially malignant disorders increased significantly with the frequency of tobacco chewing. Periodontal pockets, attrition, and loss of attachment significantly increased with the duration of the chewing habit.